"The Only Way We'll Be Successful": Organizational Factors That Influence Psychosocial Well-Being and Self-Care Among Advocates Working to Address Gender-Based Violence. Issue 23 (December 2021) - Cayir, Ebru; Spencer, Mindi; Billings, Deborah; Hilfinger Messias, DeAnne K.; Robillard, Alyssa; Cunningham, Tim
Advocates who work for nonprofit organizations (NPOs) that address gender-based violence (GBV) experience a wide range of psychosocial health and well-being risks due to the emotionally demanding nature of the work they engage in. Most recommendations for advocates' self-care focus on individual-level activities, failing to hold the NPOs accountable for creating workplace cultures and practices that foster psychosocial well-being, self-care, and resilience among the advocates. The aim of this qualitative research was to further our understanding of organizational-level factors that influence psychosocial well-being and self-care practices among advocates who work for GBV-specific NPOs in a metropolitan area in the southeastern United States. We conducted in-depth interviews with 25 GBV-specific advocates. Constructivist grounded theory methods were used in coding and analyzing the data. Sixteen advocates identified as White, followed by five Black, two Hispanic, and two mixed-race/ethnicity. Mean age was 36 years. Most participants had a master's degree ( n = 16). Analysis of the data resulted in three major themes: (a) Management and Leadership Style, (b) Interpersonal Relationship Dynamics, and (c) Culture of Self-Care. The ways in which leaders established relationships with other advocates to accomplish organizational goals, how advocates developed a sense of camaraderie with their coworkers, and shared norms around self-care shaped advocates' willingness and ability to engage in individual and collective self-care. Findings of this study highlight the role of GBV-specific NPOs in creating workplace cultures and practices that are conducive to engaging in self-care and developing resilience among the advocates. By fulfilling this responsibility, organizations would enable the advocates to not only survive, but thrive in their work and make even greater strides in the overall mission of GBV prevention.